Self-Reported Symptoms of Depression and Anxiety After ACL Injury: A Systematic Review. Issue 1 (18th January 2022) - Piussi, Ramana; Berghdal, Tora; Sundemo, David; Grassi, Alberto; Zaffagnini, Stefano; Sansone, Mikael; Samuelsson, Kristian; Senorski, Eric Hamrin
Background: Depression and anxiety symptoms can occur in patients following an anterior cruciate ligament (ACL) injury, and the presence of these symptoms has been associated with poorer self-reported knee function in this type of injury. Purpose: To investigate the prevalence and severity of self-reported symptoms of depression and anxiety following an ACL injury. Study Design: Systematic review; Level of evidence, 4. Methods: PubMed, Cochrane Library, Embase, PsycINFO, AMED, and PEDro databases were searched using a combination of keywords relating to ACL, depression, anxiety, and their synonyms. Inclusion criteria were clinical studies written in English that reported on patients with an injured and/or reconstructed ACL and assessed symptoms of depression and/or anxiety. Data extraction was performed independently by 2 authors. Data synthesis was performed using an emergent synthesis approach. The quality of the included studies was assessed using the methodological index for non-randomized studies or the Mixed-Methods Appraisal Tool. Certainty of evidence was determined using the Grading of Recommendations Assessment, Development and Evaluation. Results: After abstract screening, 37 studies were assessed in full text, of which 16 were included. The studies comprised 682 patients (417 male [61%]). The depression symptoms appeared to be more severe in elite athletes compared with recreational athletes. Symptoms decreased over time from moment of ACL reconstruction to up to 2 years postoperatively. The prevalence of self-reported symptoms of anxiety after an ACL injury was reported in 1 study (2%). There were no differences in anxiety symptoms between professional and amateur athletes or between adolescents and adults. The overall quality of the studies was low or very low. Conclusion: Patients who sustain an ACL injury can suffer from symptoms of depression, especially during the first 6 weeks after ACL reconstruction. Depressive symptoms are more common among professional versus nonprofessional athletes. Levels of anxiety symptoms were not above the cutoffs for a diagnosis of anxiety after an ACL injury.